UNDERSTANDING POETRY THROUGH THE USE OF COOPERATIVE LEARNING MODEL - Dina Ramadhanti; Diyan Permata Yanda (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: This study describes the learning process of inner and physical structure of poetry understanding through the use of Student Team Achievement and Division (STAD) and Cooperative Integrated Reading and Composition (CIRC) cooperative learning models. In addition to the cooperative learning models, literary reading interest is also used as a consideration in the learning process of poetry understanding. This experimental study involved 63 samples from a total of 124 people. Samples were randomly selected and assigned into two experimental groups. The experimental group I, with a total of 33 subjects, was treated with the STAD model, while the experimental group II, with a total of 30 subjects, was treated with the CIRC model. The subjects in the two experimental groups were assigned to complete a literary reading interest questionnaire. After the treatment, a poetry understanding test was given to the subjects in the two groups. A t-test was subsequently used to examine the students learning outcome, by considering their interest in literary reading. The results of data analysis showed no significant differences in the application of cooperative learning models in poetry understanding. Both students with high and low literary reading interest found the learning models helpful in improving their performance in the understanding inner and physical structure of poetry. Students with low literary reading interest were motivated in the learning process as a result of the teamwork in completing the poetry understanding tasks. Keywords: poetry understanding, cooperative learning, literary reading interest PEMAHAMAN PUISI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF Abstrak: Penelitian ini mendeskripsikan proses pembelajaran memahami struktur batin dan struktur fisik puisi menggunakan model pembelajaran kooperatif tipe Student Team Achievement and Division (STAD) dan Cooperative Integrated Reading and Composition (CIRC). Selain menerapkan model pembelajaran kooperatif, minat baca sastra juga menjadi pertimbangan dalam proses pembelajaran memahami puisi. Penelitian eksperimen ini dilakukan pada 63 orang sampel dari 124 orang populasi. Sampel dipilih secara acak dan ditugaskan ke dalam dua kelompok eksperimen. Kelompok eksperimen I dengan jumlah partisipan 33 orang diberikan perlakuan dengan model STAD dan kelompok eksperimen II dengan jumlah partisipan 30 orang diberikan perlakuan dengan model CIRC. Sampel pada kedua kelompok eksperimen diminta untuk mengisi angket minat baca sastra. Setelah diberikan perlakuan, sampel pada kedua kelompok eksperimen mengerjakan tes pilihan ganda memahami puisi. Hasil belajar kedua kelompok dengan menggunakan uji t-test dibandingkan dengan pertimbangan minat baca sastra. Hasil analisis data menunjukkan tidak terdapat perbedaan yang signifikan dari penerapan model pembelajaran kooperatif dalam proses memahami puisi. Model pembelajaran yang digunakan dapat membantu meningkatkan kinerja siswa dalam memahami struktur batin dan struktur fisik puisi, baik mahasiswa dengan minat baca sastra tinggi maupun mahasiswa dengan minat baca rendah. Mahasiswa yang memiliki minat baca sastra rendah termotivasi dalam proses pembelajaran karena adanya kerjasama tim dalam menyelesaikan tugas-tugas belajar memahami puisi. Kata Kunci: pemahaman puisi, pembelajaran kooperatif, minat baca sastra